2022
DOI: 10.7717/peerj.12861
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi increase crop yields by improving biomass under rainfed condition: a meta-analysis

Abstract: Background Rainfed agriculture plays key role in ensuring food security and maintain ecological balance. Especially in developing areas, most grain food are produced rainfed agricultural ecosystem. Therefore, the increase of crop yields in rainfed agricultural ecosystem becomes vital as well as ensuring global food security. Methods The potential roles of arbuscular mycorrhizal fungi (AMF) in improving crop yields under rainfed condition were explored based on 546 pairs of observations published from 1950 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 113 publications
(131 reference statements)
1
12
0
Order By: Relevance
“…Also, AM fungi improve yield and its components as it provides an adequate supply of mineral nutrients and accelerates the water and nutrient transfer from root to the stem, the increment in active nodule formation, the dry weight of the plant, and thereby increasing seed yield and its attributes. This is in agreement with Wu et al (2022) who declared that the application of AMF increased crop yields by boosting shoot biomass due to the amelioration of plant nutrition, photosynthesis, and stress resistance in the rainfed field. Many previous studies have indicated that inoculation with AMF imparts other benefits to plants, including enhanced photosynthesis rate, production of secondary metabolites like phytohormones, amino acids, vitamins, mineralization, and solubilization processes, the osmotic adjustment under stress and increased resistance against abiotic and biotic stresses as well as improving water use efficiency (Pereira et al, 2019;Komeil and Badry, 2021;Yousry et al, 2021).…”
Section: Effect Of Amf Inoculumsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, AM fungi improve yield and its components as it provides an adequate supply of mineral nutrients and accelerates the water and nutrient transfer from root to the stem, the increment in active nodule formation, the dry weight of the plant, and thereby increasing seed yield and its attributes. This is in agreement with Wu et al (2022) who declared that the application of AMF increased crop yields by boosting shoot biomass due to the amelioration of plant nutrition, photosynthesis, and stress resistance in the rainfed field. Many previous studies have indicated that inoculation with AMF imparts other benefits to plants, including enhanced photosynthesis rate, production of secondary metabolites like phytohormones, amino acids, vitamins, mineralization, and solubilization processes, the osmotic adjustment under stress and increased resistance against abiotic and biotic stresses as well as improving water use efficiency (Pereira et al, 2019;Komeil and Badry, 2021;Yousry et al, 2021).…”
Section: Effect Of Amf Inoculumsupporting
confidence: 91%
“…AMF is a vital part of soil microorganisms because it raises plant resistance to drought and improves the water use efficiency of crops by increasing the surface root area in the soil and supporting alternative physiological pathways (Abdoulaye et al, 2022). Inoculation of plants with AMF resulting increased crop yields by 23.0% owing to the increase in plant growth and nutrient uptake, photosynthesis, and drought stress resistance (Wu et al, 2022), improved soil structure (Youssef et al, 2017), and promoted crop quality and productivity (Begum et al, 2019). Egypt is placed in an arid and semi-arid area, water scarcity and its use efficiency are considered essential factors that directly affect the productivity of many crops globally (Orabi et al, 2021), and crops need water for all physiological processes i.e., photosynthesis, nutrient uptake, and other metabolic processes, and about 400-500 liter of water is necessary for the production of 1 Kilo from plant dry matter (Attri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…AMF treatment can increase root biomass higher than stem biomass, namely 24.2% in stems and 29.6% in roots. Wu et al (2022) reported that the increase in biomass by AMF treatment depended on the organ type and functional group of the host plant (e.g., grain and non-grain, N-fixing, and non-N-fixing). The increase in plant stem biomass by AMF treatment was greater in non-grain plants, which was 54.9%, while in grain plants there was only a 17.4% increase.…”
Section: Growth Performancementioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) are obligate biotrophs that form endosymbiotic associations with the roots of vascular plants, including various crops [ 19 , 20 ]. AMF enhance the mineral nutrient uptake [ 21 , 22 ] and photosynthesis of host plants [ 22 ], decrease disease invasion [ 23 ], induce tolerance to extreme temperature changes [ 24 ], reduce heavy metal toxicity [ 25 ], and confer drought stress tolerance. The positive effects of AMF on antioxidant [ 26 ], polyamine production [ 27 ], osmotic adjustment [ 28 ], plant development [ 29 ], drought tolerance in host plants [ 30 ], and water transport [ 31 ] have been previously reported in various plants exposed to drought.…”
Section: Introductionmentioning
confidence: 99%